Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

y = (x + 2)(x − 3)
Find the zero of the function


Sagot :

Answer:

The zeros are {-2, 3}

Step-by-step explanation:

Set each of these factors equal to zero, in turn, set each factor = to 0 and solve the resulting equation for x:

x + 2 = 0 yields x = -2;

x - 3 = 0 yields x = 3

The zeros are {-2, 3}